Relationship between the Position of the Mandibular Third Molar with Different Vertical Skeletal Dimensions on the Panoramic Images in Patients Referred to Isfahan (Khorasgan) University Dental School - Fatemeh Eskandari; Nasim Esnaashari; Roshanak Ghaffari; Seyedeh Leila MousavizadehMobarakeh (Isfahan University of Medical Sciences, 2022)
Due to the increased prevalence of third molar impaction and the complications and existence of disagreements regarding the predicting factors for the impaction of this tooth, the aim of this study was to evaluate the relationship between the position of the mandibular third molar with different vertical skeletal dimensions on the panoramic images.Materials & Methods:This cross sectional study was carried out on lateral cephalogram and orthopantomogram records of 130 orthodontic patients visiting to Isfahan (Khorasgan) University Dental School. Age range of the sample was 20-35 years. Various facial forms were determined with mandibular plane angle (SN-GoGn), jarabak index and Y-axis; S-GN-Frankfort plane. Beta angle; which is the angle between intersecting long axis of mandibular second molar and mandibular third molar was measured to determine the angle of eruption of mandibular third molar. Eruption pattern was classified as per Pell & Gregory and winter's system. The data were analyzed by Chi-square test (p value < 0.05).Results:There was a significant difference in the frequency distribution of growth pattern on the left side of the jaw (p value = 0.048). There was no significant difference in the frequency distribution of the eruption pattern in the right side of the jaw (p value = 0.11).There was no significant difference in the frequency distribution of eruption surface in the right face between different facial forms (p value = 0.49) But on the left side of the jaw there was a significant difference between the three facial forms (p value = 0.049). Frequency distribution of mandibular third molar impaction was significantly different between the three facial forms (p value = 0.03). There was no significant difference between the three facial forms in terms of frequency of eruption angle in the right side of the jaw (p value = 0.25) and also in the left side of the jaw (p value = 0.15).Conclusion:The incidence of impaction was significantly more in patients with long face than in other two groups. The prevalence of surface and pattern of third molar eruption in only one side of jaw was significantly different between the three facial forms. There was no significant difference between the frequency of angle of eruption and facial skeletal types in both jaws